CURRENT SPECTRUM OF GENERALISED PERITONITIS - Afridi, Shahjehan; Sultan, Syed; Ahmad, Rashid (Journal of Ayub Medical College Abbottabad, 1992)
One hundred twenty-one consecutive cases of Generalised peritonitis under two General Surgical Units were studied retrospectively. The aetiology and outcome were documented to know the spectrum and compared with other reported series. The most common cause was typhoid perforations of which there were thirty-five cases. The second common cause was perforated Appendicitis of which there were twenty eight cases. The third largest group of peritonitis was due to Gangrene of Gut of which there were 18 cases. The 4th most common cause was duodenal ulcer perforation of which there were sixteen cases. The miscellaneous group consisted of twenty-four cases. Over-all mortality was 18%. It is notable that only two deaths occurred in patient with peritonitis associated with Appendicitis. There were 73 male and 48 female patients. The death ratio male to female was 2:1 (14 males and 7 female).